The Soviet Federation - Poliakov, Jurij A. (Czasopismo Prawno-Historyczne, 1980)
The Union of Soviet Socialist Republics is a multinational state. According to the 1970 census, there are more than 100 nations and nationalities in the Soviet Union, with 22 of them numbering over 1 million people, 27 between 100 thousand and 1 million, and 28 between 10 and 100 thousand. In 1970, the Russian population accounted for 53.4 per cent of the entire population, Ukrainian 16.9 per cent, Uzbek 3.8 per cent, Byelorussian 3.7 per cent, Tatar 2.4 per cent, Kazakh 2.2 per cent, Azerbaijan 1.8, Armenian 1.5 per cent, Georgian 1.3 per cent, Lithuanian 1.1 per cent, Moldavian 1.1, Jewish 0.9, and Tajik 0.9 per cent. The Soviet Union has gained a wealth of experience in establishing the state federative system both for the country as a whole and for every individual republic. The Soviet socialist federation, which has become a state form of solving the national problem, is a new type of a federative system. Federation in the Soviet Union includes two forms, that is, the treaty federation, or the association of equal Union republics forming an integral federal state, the Union of Soviet Socialist Republics, and the federation based on the national and territorial autonomy uniting nationalities with a different state and legal status (such as, autonomous Soviet socialist republics, autonomous regions, and national districts). According to the 1977 Constitution of the Soviet Union, "The Union of Soviet Socialist Republics is an integral, federal, multinational state formed on the principle of socialist federalism as a result of the free self-determination of nations and the voluntary association of equal Soviet Socialist Republics" (Article 70).